The prevalence and risk factors for urinary incontinence among inpatients, a multicenter study from Turkey - TUFAN ÇİNÇİN, ASLI (ELSEVIER IRELAND LTD, 2020)
Objective: To determine the prevalence and the factors associated with urinary incontinence (UI) among inpatients in Turkey. Method: The population of this study comprised of patients screened by the National Prevalence Measurement of Quality of Care (LPZ) study in 2017 and 2018. Age, gender, comorbidities, length of hospital stay, sedative medications, SARC-F score, anthropometric measurements, and care parameters such as malnutrition, falls, UI-fecal incontinence (FI), restraints, and care dependency score (CDS) were noted. The LPZ questionnaire was performed by trained researchers, and multiple logistic regression analysis was performed to determine the factors associated with UI. Results: The prevalence of UI was 29.4 % among 1176 inpatients, and 41.6 % in patients >= 65 years. Urinary incontinence was associated with older age (OR, 1.966, 95 % CI 1.330-2.905), female sex (OR, 2.055, 95 % CI 1.393-3.030), CDS (OR, 3.236, 95 % CI 2.080-5.035), the number of comorbidities (OR, 1.312, 95 % CI 1.106-1.556), end-of life management (OR, 3.156, 95 % CI 1.412-7.052), sedative medications (OR, 1.981, 95 % CI 1.230-3.191), and FI (OR, 12.533, 95 % CI 4.892-32.112) in all adults, where CDS (OR, 2.589, 95% CI 1.458-4.599), end-of life management (OR, 2.851, 95 % CI 1.095-7.424), sedative medications (OR, 2.529, 95 % CI 1.406-4.548), and FI (OR, 13.138, 95 % CI 4.352-39.661) were associated with UI among geriatric patients. Conclusions: The factors associated with UI in geriatric and all adult inpatients are CDS, sedative medications, end-of life management, and FI plus older age, female sex, and comorbidities for the latter. The factors associated with UI vary in different age groups.
Keywords: Urinary incontinence; Hospitalization; Risk factor; Older adults; Prevalence; OVERACTIVE BLADDER; CARE DEPENDENCY; OLDER-PEOPLE; WOMEN; QUESTIONNAIRE; ASSOCIATION; SCALE; FALLS; MEN